Penggunaan Model Edukasi Berbasis Aplikasi Mobile Eduma terhadap Perubahan Pengetahuan dan Kepatuhan Ibu Hamil Mengkonsumsi Tablet Tambah Darah - Permatasari, Chyntia Punky; Widyawati, Melyana Nurul; Ramlan, Djamaluddin; Supriyadi, Supriyadi (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the application of an educational model by combining alarms and reminder notifications to consume blood supplement tablets based on a mobile application called EDUMA to change pregnant women's knowledge and compliance with consuming blood supplement tablets. The method used was a quasi-experiment with a one-group pre-test-post-test design. The research results showed that the knowledge difference test obtained a p-value of 0.045 and compliance of 1.000. The conclusions of this research show that the only thing that has a significant difference before and after using the "EDUMA" mobile application-based educational model for 21 days is the knowledge variable. Keywords: Applications, Compliance, Knowledge